New records in the Tubeufiaceae from Andean Patagonian forests of Argentina - Sanchez, Romina Magali; Bianchinotti, Maria Virginia (Mycotaxon)
Tubeufiaceae (Pleosporales, Ascomycota) occurring on native trees from the Andean Patagonian forests in Argentina are described and illustrated. Acanthostigma minutum and Tubeufia cerea with its anamorphic state are reported from South America for the first time on Nothofagus dombeyi and N. antarctica, respectively. Both species were up to now only known from the Northern Hemisphere. Fil: Sanchez, Romina Magali. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Centro de Recursos Naturales Renovables de la Zona Semiarida. Universidad Nacional del Sur. Centro de Recursos Naturales Renovables de la Zona Semiarida; Argentina Fil: Bianchinotti, Maria Virginia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Centro de Recursos Naturales Renovables de la Zona Semiarida. Universidad Nacional del Sur. Centro de Recursos Naturales Renovables de la Zona Semiarida; Argentina